Multiproduct Firms: A Nested Logit Approach - Simon P. Anderston; Andre de Palma (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Thie paper proves the existence of a symmetric equilibrium with multiproduct firms using a nested logit model of demand. The demand model is parametrized by two variable which characterize different dimensions of preference variety. These reflect intragroup heterogeneity and intergropu heterogeneity, a group (or nest) being the set of products produced by a firm. There are then two dimensions to market performance; the total number of firms and the range of products produced per firm. It is shown that the market equilibrium involves an excessive number of firms, but each firm provides too few products.
Keywords: O11; 330; Discrete choice model; oligopolistic competition; multiple product firms; nested logit model